Current perspectives in herbal and conventional drug interactions based on clinical manifestations - Ajaykumar Rikhabchand Surana; Shivam Puranmal Agrawal; Manoj Ramesh Kumbhare; Snehal Balu Gaikwad (SpringerOpen, 2021)
Abstract Background Herbs are an important source of pharmaceuticals. Herbs are traditionally used by millions of peoples for medicine, food and drink in developed and developing nations considering that they are safe. But, interaction of herbs with other medicines may cause serious adverse effects or reduces their efficacy. The demand for "alternative" medicines has been increased significantly, which include medicine derived from plant or herbal origin. The objective of this review article mainly focuses on drug interactions of commonly used herbs along with possible mechanisms. The method adopted for this review is searching of herb-drug interactions in online database. Main text Herb-drug interaction leads to pharmacological modification. The drug use along with herbs may show pharmacodynamic and pharmacokinetic interactions. Pharmacokinetic interaction causes alteration in absorption, distribution, metabolism and elimination. Similarly, pharmacodynamic interaction causes additive or synergistic or antagonist effect on the drugs or vice versa. Researchers had demonstrated that herbs show the toxicities and drug interactions like other pharmacologically active compounds. There is lack of knowledge amongst physician, pharmacist and consumers related to pharmacological action and mechanism of herb-drug interaction. This review article focuses on the herb-drug interaction of danshen (Salvia miltiorrhiza), Echinacea (Echinacea purpurea), garlic (Allium sativum), ginkgo (Ginkgo biloba), goldenseal (Hydrastis canadensis), green tea (Camellia sinensis), kava (Piper methysticum), liquorice (Glycyrrhiza glabra), milk thistle (Silybum marianum) and St. John's wort (Hypericum perforatum) along with probable mechanisms and clinical manifestation based on case studies reported in literature. Conclusion Herb-drug interactions may lead to serious side effects. Physician, pharmacist and patients must be more cautious while prescribing and or consuming these herbs.